The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1108/02644400410565306
|View full text |Cite
|
Sign up to set email alerts
|

Computation of weakly‐compressible highly‐viscous liquid flows

Abstract: We introduce a high-resolution time-marching pressure-correction algorithm to accommodate weakly-compressible highly-viscous polymeric liquid flows at low Mach number. As the incompressible limit is approached ( 0 ≈ Ma ), the consistency of the compressible scheme is highlighted in recovering equivalent incompressible solutions. In retention, yet efficiency in implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Taliadorou et al (2008) simulated the extrusion of strongly compressible Newtonian liquids and found that compressibility can lead to oscillatory steady-state free surfaces. Webster et al (2004) introduced numerical algorithms for solving weakly compressible, highly viscous laminar Newtonian flows at low Mach numbers. They applied their methods to the driven cavity and the contraction flow problems.…”
Section: Introductionmentioning
confidence: 99%
“…Taliadorou et al (2008) simulated the extrusion of strongly compressible Newtonian liquids and found that compressibility can lead to oscillatory steady-state free surfaces. Webster et al (2004) introduced numerical algorithms for solving weakly compressible, highly viscous laminar Newtonian flows at low Mach numbers. They applied their methods to the driven cavity and the contraction flow problems.…”
Section: Introductionmentioning
confidence: 99%
“…This finally results in no change in mean density due to compression and the flow becomes incompressible in the limit, irrespective of the fact that there may still be some large density variations due to non-homogeneous entropy distributions. This necessitates a modified solver algorithm with Mach-uniform accuracy and efficiency, applicable to both compressible and incompressible regimes inside a flow device [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Edwards and Beris [5] adopt a weakly compressible framework so the issue is perhaps not as pertinent there. Webster et al [19] use the static pressure, but in later papers adopt the use of augmented pressure in the equation of state (see [1,9]), presumably recognising that augmented pressure,p, has more physical significance than static pressure, p, within a dynamic setting. Of course, in an isotropic fluid at equilibrium in a region containing a free surface, the two pressure fields are equal since the isotropic part of the extra stress vanishes.…”
Section: Introductionmentioning
confidence: 99%